2010
DOI: 10.1128/aac.01306-09
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotide Interactions with the Nematode External Surface

Abstract: Cyclotides are a large family of cyclic cystine knot-containing plant peptides that have anthelminthic activities against Haemonchus contortus and Trichostrongylus colubriformis, two important gastrointestinal nematodes of sheep. In this study, we investigated the interaction of the prototypic cyclotide kalata B1 with the external surface of H. contortus larvae and adult worms. We show that cyclotides do not need to be ingested by the worms to exert their toxic effects but that an interaction with the external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…The natural function of cyclotides in plants seems to be as host-defense agents as deduced from their activity against insects [21, 22], nematodes [28, 29, 113, 114], and mollusks [60]. For example, it has been shown that cyclotides can efficiently inhibit the growth and development of insect and nematode larvae [115].…”
Section: The Discoverymentioning
confidence: 99%
“…The natural function of cyclotides in plants seems to be as host-defense agents as deduced from their activity against insects [21, 22], nematodes [28, 29, 113, 114], and mollusks [60]. For example, it has been shown that cyclotides can efficiently inhibit the growth and development of insect and nematode larvae [115].…”
Section: The Discoverymentioning
confidence: 99%
“…3 | Issue 3 | Jul-Sep 2012  172  novel drugs and biopesticides. [34,35] The speculated natural function of cyclotides is in plant defense as illustrated by several reports of their antibacterial/antimicrobial, [36] insecticidal, [37,38] antihelmintic, [39][40][41] nematocidal, [42] antifouling, [43] and molluscicidal properties. [44] The use of cyclotides in human health applications was first explored during the discovery of kalata B1, and although its uterotonic activity was established in rat, rabbit, and human uteri, it is not recommended as an oxytocic agent because of the severe side effects.…”
Section: Biologically Active Properties Of Cyclotidesmentioning
confidence: 99%
“…[47,50,52,[69][70][71][72][73] For instance, reports indicate that kalata peptides selectively bind to bacterial membranes, [69,74] and some cyclotides may form discrete pores on the external surface of nematodes and thereby interact with the lipid-rich epicuticle layer at the surface of the worm. [42] Furthermore, the antitumor properties of cyclotide, cycloviolacin O 2 (CyO 2 ) are caused first by the disruption of lipid membranes followed by leakage of contents from whole cells as well as liposomes. [70] CyO 2 causes rapid (within 5 minutes) disruption of lipid bilayers and is selectively cytotoxic in a dose-dependent manner.…”
Section: Structural and Molecular Features Of Cyclotides Impact Bioacmentioning
confidence: 99%
“…56 These results indicated the structural regions involved in nematicidal activity and suggested that the inclusion of epitopes in loops helps in interaction with the membrane. 56,57 Antimicrobial Activity Bactericidal activity is an important function related to the cyclotide family. The cyclotides circulin B and cyclopsychotride A show antimicrobial activities against Escherichia coli and Pseudomonas aeruginosa.…”
Section: Pinto Et Al 47mentioning
confidence: 99%